MSA-3D: Metallicity Gradients in Galaxies at z ∼ 1 with JWST/NIRSpec Slit-stepping Spectroscopy - Mengting Ju; Xin Wang; Tucker Jones; Ivana Barišić; Themiya Nanayakkara; Kevin Bundy; Claude-André Faucher-Giguère; Shuai Feng; Karl Glazebrook; Alaina Henry; Matthew A. Malkan; Danail Obreschkow; et al. (The Astrophysical Journal Letters)
The radial gradient of gas-phase metallicity is a powerful probe of the chemical and structural evolution of star-forming galaxies, closely tied to disk formation and gas kinematics in the early Universe. We present spatially resolved chemical and dynamical properties for a sample of 25 galaxies at 0.5 ≲  z  ≲ 1.7 from the MSA-3D survey. These innovative observations provide 3D spectroscopy of galaxies at a spatial resolution approaching JWST’s diffraction limit and a high spectral resolution of R  ≃ 2700. The metallicity gradients measured in our galaxy sample range from −0.03 to 0.02 dex kpc ^−1 . Most galaxies exhibit negative or flat radial gradients, indicating lower metallicity in the outskirts or uniform metallicity throughout the entire galaxy. We confirm a tight relationship between stellar mass and metallicity gradient at z  ∼ 1 with small intrinsic scatter of 0.02 dex kpc ^−1 . Our results indicate that metallicity gradients become increasingly negative as stellar mass increases, likely because the more massive galaxies tend to be more “disky.” This relationship is consistent with the predictions from cosmological hydrodynamic zoom-in simulations with strong stellar feedback. This work presents the effort to harness the multiplexing capability of the JWST NIRSpec microshutter assembly in slit-stepping mode to map the chemical and kinematic profiles of high-redshift galaxies in large samples and at high spatial and spectral resolution.